PERAN UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MELINDUNGI KEKERASAN ANAK DI TANZANIA ( 2011-2014) - Diah Mutiara Kartika; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to understand how Role of the United Nations Children's Fund (UNICEF) Protection of Children From Violence in Tanzania 2011-2014. Tanzania was the first country in Africa to undertake a comprehensive survey on prevalence levels of sexual, physical and emotional violence against girls and boys. The Tanzania Violence Against Children Study, released by the Government and UNICEF in 2011, reveals that one in three girls and one in seven boys in Tanzania experiences sexual violence before the age of eighteen. In addition, rates of physical violence are alarmingly high, nearly three out of four boys and girls experience being punched, whipped or kicked during their childhood, while one quarter of all children are emotionally abused. The majority of children do not report their experience, few seek services, and even fewer actually receive any care, treatment or support. The initiative supported by the joint-project is a follow-up to the Violence Against Children Study undertaken in 2009 that will help the country move from research to action.This research theoretically has built with Pluralism Perspective on International Relations and supported by International Organization theory, and also the concept of Role Model. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library.Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis whic reveals the fact that Role of the United Nations Children's Fund (UNICEF) Protection of Children From Violence in Tanzania 2011-2014 are making the program "Save the Children", UNICEF and other UN agencies have joined the World Bank and Department for International Development (DfID), UNICEF is working with NGOs in Tanzania in the Children's Agenda, as well as the Government Project Tanzania, UNICEF, EU, SCI, and PLAN in Child Protection Initiative.Keywords : International Organization, Role, UNICEF, Child Protection, Violence Children, Tanzania